Immunodominant T cell peptides from four candidate malarial antigens as biomarkers of protective immunity against malaria. Issue 6 (3rd February 2023) - Belmonte, Maria; Ganeshan, Harini; Huang, Jun; Belmonte, Arnel; Inoue, Sandra; Velasco, Rachel; Acheampong, Neda; Ofori, Ebenezer Addo; Akyea-Mensah, Kwadwo; Frimpong, Augustina; Ennuson, Nana Aba; Frempong, Abena Fremaah; et al.
Highlights: 135 T cell epitopes identified in four P. falciparum antigen, with 75 % being novel. Thirty-two percent (32%) of the 135 epitopes show promiscuity in HLA binding. Fifty-two percent (52%) are conserved across 16 highly diverse parasite variants. CSP and AMA1 had greater numbers of T cell epitopes compared to TRAP and CelTOS. Abstract: A malaria vaccine with high efficacy and capable of inducing sterile immunity against malaria within genetically diverse populations is urgently needed to complement ongoing disease control and elimination efforts. Parasite-specific IFN-γ and granzyme B-secreting CD8 + T cells have been identified as key mediators of protection and the rapid identification of malaria antigen targets that elicit these responses will fast-track the development of simpler, cost-effective interventions. This study extends our previous work which used peripheral blood mononuclear cells (PBMCs) from adults with life-long exposure to malaria parasites to identify immunodominant antigen-specific peptide pools composed of overlapping 15mer sequences spanning full length proteins of four malarial antigens. Our current study aimed to identify CD8 + T cell epitopes within these previously identified positive peptide pools. Cryopreserved PBMCs from 109 HLA-typed subjects were stimulated with predicted 9-11mer CD8 + T cell epitopes from P. falciparum circumsporozoite protein (CSP), apical membrane antigen 1 (AMA1), thrombospondin related anonymous protein (TRAP) and cell traversal for ookinetes and sporozoites (CelTOS) in FluoroSpot assays. A total of 135 epitopes out of 297 tested peptides from the four antigens were experimentally identified as positive for IFN-γ and/or granzyme B production in 65 of the 109 subjects. Forty-three of 135 epitopes (32 %) were promiscuous for HLA binding, with 31 of these promiscuous epitopes (72 %) being presented by HLA alleles that fall within at least two different HLA supertypes. Furthermore, about 52 % of identified epitopes were conserved when the respective sequences were aligned with those from 16 highly diverse P. falciparum parasite strains. In summary, we have identified a number of conserved epitopes, immune responses to which could be effective against multiple P. falciparum parasite strains in genetically diverse populations.